The many faces of multi-level issues - Yammarino, Francis J., 1954-; Dansereau, Fred, 1946- (Emerald, 2002)
This title is part of a series that aims to present timely, scholarly work on multiple levels of analysis, multi-level theory, research, and methods. The focus is on 'critical essays', theoretical work, empirical studies, methodological developments, analytical techniques, and philosophical treatments.
Keywords: Organizational behavior.; Management.; Personnel management.; elektronické knihy; electronic books